Marketing strategy through TikTok social media at Nura Catering - Halwa Salsilah; Heri Setiawan; Dewi Fadila (Universitas Pendidikan Indonesia, 2025)
The rapid development of digital technology has transformed consumer behavior, making social media a key channel for product marketing. However, many Micro, Small, and Medium Enterprises (MSMEs) have yet to harness this potential fully. Nura Catering, a catering service business in Palembang, is one such example, still relying on conventional promotion methods and lacking active engagement on digital platforms. This community service project aimed to enhance the partner’s capability in leveraging TikTok as a digital marketing tool. The program adopted a participatory approach through intensive training and mentoring, covering profile optimization, content planning, video production, and performance analysis using TikTok Analytics. The results showed a significant improvement in social media management skills, reflected in increased reach, engagement, and follower growth within one month. Additionally, the partner successfully produced independent content in accordance with the implemented strategy. Overall, the program had a positive impact on brand visibility and strengthened the competitiveness of MSMEs in the digital era. Abstrak Perkembangan teknologi digital telah mengubah pola konsumsi masyarakat, menjadikan media sosial sebagai salah satu saluran utama pemasaran produk. Namun, sebagian besar Usaha Mikro, Kecil, dan Menengah (UMKM) belum mampu memanfaatkan potensi ini secara optimal. Salah satunya adalah Nura Catering, UMKM yang bergerak di bidang jasa boga di Kota Palembang yang masih mengandalkan metode promosi konvensional dan kurang aktif di platform digital. Kegiatan pengabdian ini bertujuan untuk meningkatkan kemampuan mitra dalam memanfaatkan TikTok sebagai media pemasaran digital. Metode yang digunakan meliputi pendekatan partisipatif melalui pelatihan dan pendampingan intensif, mulai dari optimalisasi profil akun, perencanaan konten, pembuatan video, hingga analisis performa menggunakan fitur TikTok Analytics. Hasil kegiatan menunjukkan peningkatan signifikan dalam keterampilan pengelolaan media sosial mitra, terlihat dari bertambahnya jangkauan audiens, tayangan video, dan jumlah pengikut dalam satu bulan. Selain itu, mitra mampu membuat konten secara mandiri sesuai strategi yang telah dirancang. Program ini memberikan dampak positif terhadap peningkatan visibilitas merek dan memperkuat daya saing UMKM di era digitalisasi. Kata Kunci: digital marketing; Nura Catering; TikTok; UMKM